Electrolyte and sodium ion battery containing same
By adding lithium salts and acid anhydride organic compounds to the electrolyte of sodium ion batteries, a strong coordination structure was formed, which solved the problem of thickening during the dissolution-regeneration of SEI membrane, and improved the migration ability of sodium ions, realizing the battery Improved cycle performance.
Patent Information
- Application Number
- CN202411602249.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The SEI membrane of existing sodium ion batteries is constantly dissolved and regenerated during the cycle, causing the membrane to gradually thicken, affecting battery performance, and the addition of lithium salts may hinder sodium ion migration.
By adding an appropriate amount of lithium salt and acid anhydride organic compounds to the electrolyte, the molar ratio is controlled to form a strong coordination structure, increasing the oxygen content in the SEI film, reducing the content of lithium fluoride, and increasing sodium ions in the SEI film migration capability.
It effectively slows down the dissolution-regeneration process of the SEI membrane, improves the cycling performance of the battery, and does not affect the battery capacity, ensuring the migration ability of sodium ions.
Smart Images

Figure CN119447457A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of sodium ion batteries, and in particular to an electrolyte and a sodium ion battery containing the electrolyte. Background Art
[0002] With the rapid development of electronic devices, electric vehicles and smart grids, advanced battery technology plays an increasingly important role in modern society, and safe energy storage systems are in great demand worldwide. Sodium is abundant in resources and cheap in price, so sodium-ion batteries are expected to be used in large-scale energy storage. Carbon-based negative electrodes have always had great application prospects. Traditional graphite anodes have great application limitations due to their inability to reversibly insert / extract sodium ions. Hard carbon materials have the advantages of high theoretical capacity and low reaction potential, and have received widespread attention in recent years. However, the low Coulomb efficiency of hard carbon materials in the first cycle and the rapid decrease in capacity limit their application. A common strategy is to generate a solid electrolyte interface film (SEI film) with excellent performance to prevent further side reactions between the electrolyte and the negative electrode.
[0003] As far as the current electrolyte composition is concerned, most sodium salt anions contain fluorine, and fluorinated solvents are usually used to improve the oxidative stability of the original solvent. In ester electrolytes, sodium fluoride is an easily generated inorganic substance and an important component of the SEI membrane of sodium ion batteries. However, sodium fluoride has a certain solubility in ester electrolytes, which causes the SEI membrane of sodium ion batteries to be continuously dissolved and regenerated during the cycle. As the cycle progresses, the SEI membrane gradually thickens, and in this process, the sodium element available for circulation is also reduced.
[0004] In addition to sodium fluoride, the inorganic substances in the SEI membrane of sodium ion batteries may also include sodium oxide, sodium carbonate, etc. Although the deposition potential of lithium ions is 0.3V lower than that of sodium ions, according to literature reports, in sodium ion electrolytes containing lithium salt additives, the generated SEI membrane contains lithium inorganic substances. Adding lithium salts to the electrolyte of sodium ion batteries can generate SEI membranes containing lithium fluoride, lithium oxide, lithium carbonate and other substances. The solubility of lithium fluoride, lithium oxide, lithium carbonate and the like in organic solvents is lower than that of inorganic substances corresponding to sodium. Therefore, lithium inorganic substances can be introduced into the SEI membrane to slow down the rate of dissolution-regeneration of the SEI membrane. However, other literature reports that at room temperature, sodium ions can migrate normally in lithium carbonate, but are difficult to migrate in lithium fluoride, thus affecting battery performance.
[0005] Therefore, how to provide a method that can slow down the dissolution-regeneration process of the SEI film without affecting the migration of sodium ions has become an urgent problem to be solved. Summary of the invention
[0006] In order to solve the above technical problems, the present disclosure provides an electrolyte and a sodium ion battery containing the same. The electrolyte effectively improves the cycle performance while ensuring the battery capacity by adding lithium salts, anhydride organic compounds and film-forming additives to conventional electrolyte components and controlling the added amounts.
[0007] In a first aspect, the present disclosure provides an electrolyte solution, which comprises, by weight percentage, 5 to 20 wt% of a sodium salt, 70 to 94 wt% of a solvent, 0.01 to 0.5 wt% of a lithium salt, 0.1 to 5 wt% of an anhydride organic compound, and 0.1 to 5 wt% of a film-forming additive;
[0008] The molar ratio of the anhydride organic compound to the lithium salt is not less than 5.
[0009] The content of sodium salt is, for example, 5wt%, 10wt%, 15wt% or 20wt%, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0010] The content of the solvent is, for example, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt% or 94 wt%, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0011] The content of lithium salt is, for example, 0.01 wt%, 0.02 wt%, 0.05 wt%, 0.1 wt%, 0.2 wt% or 0.5 wt%, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0012] The content of the anhydride organic compound is 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other values not listed in the range are also applicable;
[0013] The content of the film-forming additive is 0.1wt%, 0.2wt%, 0.5wt%, 0.18wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0014] The molar ratio of the anhydride organic compound to the lithium salt is selected such as 5, 6, 8, 10, 12, 15, 20, 30 or 40, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0015] On the one hand, the present disclosure introduces an appropriate amount of lithium salt into the electrolyte in order to improve the stability of the SEI film of the sodium ion battery and slow down the dissolution-regeneration rate of the SEI film during the cycle; on the other hand, in order to address the problem of poor sodium ion migration ability caused by the addition of lithium salt, the present disclosure finds that sodium ions can migrate in lithium carbonate at room temperature. Based on this, the present disclosure introduces an appropriate amount of anhydride organic compound into the electrolyte. The anhydride organic compound can form a strong coordination structure with lithium ions or sodium ions, thereby increasing the oxygen content in the SEI film when the SEI film is formed, thereby reducing the content of lithium fluoride and increasing the content of lithium carbonate in the SEI film, thereby increasing the migration ability of sodium ions in the SEI film.
[0016] In addition, lithium salts and anhydride organic compounds need to be controlled. If there are too few anhydride organic compounds, there will still be a certain proportion of LiF in the SEI film, which will affect the migration of sodium ions and thus affect the battery capacity; if there are too many anhydride organic compounds, the SEI film will become thicker, affecting the rate performance of the battery cell.
[0017] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.
[0018] As a preferred technical solution of the present disclosure, the composition comprises, by weight percentage, 5-20 wt% of sodium salt, 75-90 wt% of solvent, 0.05-0.5 wt% of lithium salt, 0.25-5 wt% of anhydride organic compound and 1-3 wt% of film-forming additive;
[0019] The molar ratio of the acid anhydride organic compound to the lithium salt is 5-25.
[0020] The content of sodium salt is 5wt%, 10wt%, 15wt% or 20wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0021] The content of the solvent is 75wt%, 80wt%, 85wt% or 90wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0022] The content of lithium salt is 0.05wt%, 0.08wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.4wt% or 0.5wt%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable;
[0023] The content of the anhydride organic compound is 0.25wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0024] The content of the film-forming additive is, for example, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt% or 3 wt%, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0025] The molar ratio of the anhydride organic compound to the lithium salt is selected such as 5, 6, 8, 10, 12, 15, 20, 23 or 25, but is not limited to the listed values. Other values not listed in the range are also applicable.
[0026] As a preferred technical solution of the present disclosure, the sodium salt includes one or more of sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium hexafluoroantimonate, sodium difluorooxalatoborate, sodium bis(difluoromalonate)borate, sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethanesulfonyl)imide, such as a combination of sodium hexafluoroarsenate and sodium hexafluoroantimonate, a combination of sodium bis(trifluoromethanesulfonyl)imide and sodium bis(difluoromalonate)borate, etc.
[0027] As a preferred technical solution of the present disclosure, the solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, cyclopentane, dimethyl sulfoxide, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, methyl difluoroacetate, ethyl difluoroacetate, γ-butyrolactone, γ-valerolactone or δ-valerolactone, for example, a combination of ethylene carbonate, propylene carbonate and dimethyl carbonate, a combination of methyl propionate, ethyl propionate and propyl propionate, a combination of propyl butyrate and butyl butyrate, etc.
[0028] As a preferred technical solution of the present disclosure, the lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium hexafluoroantimonate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate or lithium fluoride, such as a combination of lithium bis(fluorosulfonyl)imide and lithium tetrafluoroborate, a combination of lithium hexafluoroarsenate and lithium hexafluoroantimonate, etc.
[0029] As a preferred technical solution of the present disclosure, the anhydride organic compound includes one or more of glutaric anhydride, citraconic anhydride, maleic anhydride, phenylmaleic anhydride, benzoic anhydride or succinic anhydride, such as a combination of glutaric anhydride and maleic anhydride, a combination of phenylmaleic anhydride and benzoic anhydride, etc.
[0030] As a preferred technical solution of the present invention, the film-forming additive includes one or more of vinylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, dimethyl sulfate, vinyl sulfate, methyl vinyl sulfate, propylene sulfate, vinyl sulfite, succinic anhydride, biphenyl, biphenyl ether, toluene, xylene, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, propylene sultone, butane sultone, methanedisulfonic acid methylene ester, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, heptamethyldisilazane, dimethyl methylphosphonate, diethyl ethylphosphonate, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, triphenyl phosphite, tris(trimethylsilyl)borate or tris(trimethylsilyl)phosphate, such as vinylene carbonate and vinyl ethylene carbonate, dimethyl sulfate and vinyl sulfate, etc.
[0031] In a second aspect, the present disclosure provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte as described in the first aspect.
[0032] As a preferred technical solution of the present disclosure, the positive electrode active material used in the positive electrode sheet includes one or more of transition metal layered oxides, polyanionic materials or Prussian blue materials, preferably polyanionic materials.
[0033] As a preferred technical solution of the present disclosure, the negative electrode active material used in the negative electrode includes one or more of carbon materials, metal materials or metal compounds, preferably carbon materials.
[0034] Preferably, the carbon material comprises a hard carbon material.
[0035] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0036] The present invention introduces lithium salts and acid anhydride organic compounds into the electrolyte. The lithium salts and acid anhydride organic compounds work synergistically, which can not only slow down the dissolution-regeneration process of the SEI film, but also do not affect the sodium ion migration process. Using it in a sodium ion battery can effectively improve the cycle performance of the battery without affecting the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0039] Figure 1 It is a comparison chart of the discharge capacity retention rate of the sodium ion batteries obtained in Examples 1-5 of the present disclosure and Comparative Examples 1-5. DETAILED DESCRIPTION
[0040] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0042] Example 1
[0043] This embodiment provides an electrolyte, including 14.9wt% sodium hexafluorophosphate, 82.5wt% solvent (prepared according to the mass ratio of ethylene carbonate (EC) / propylene carbonate (PC) / diethylene carbonate (DEC) / ethyl methyl carbonate (EMC)=1:1:1:2), 0.1wt% lithium hexafluorophosphate, 0.5wt% glutaric anhydride, 1wt% vinyl sulfate and 1wt% vinylene carbonate. The molar ratio of the anhydride organic compound to the lithium salt is 6.66.
[0044] Example 2
[0045] This embodiment provides an electrolyte, including 14.9wt% sodium hexafluorophosphate, 82.62wt% solvent (prepared according to the mass ratio of ethylene carbonate (EC) / propylene carbonate (PC) / diethylene carbonate (DEC) / ethyl methyl carbonate (EMC)=1:1:1:2), 0.1wt% lithium hexafluorophosphate, 0.38wt% glutaric anhydride, 1wt% vinyl sulfate and 1wt% vinylene carbonate. The molar ratio of the anhydride organic compound to the lithium salt is 5.06.
[0046] Example 3
[0047] This embodiment provides an electrolyte, including 14.95wt% sodium hexafluorophosphate, 82.5wt% solvent (prepared according to the mass ratio of ethylene carbonate (EC) / propylene carbonate (PC) / diethylene carbonate (DEC) / ethyl methyl carbonate (EMC)=1:1:1:2), 0.05wt% lithium hexafluorophosphate, 0.75wt% glutaric anhydride, 1wt% vinyl sulfate and 1wt% vinylene carbonate. The molar ratio of the anhydride organic compound to the lithium salt is 19.98.
[0048] Example 4
[0049] This embodiment provides an electrolyte, including 14.9wt% sodium hexafluorophosphate, 82.99wt% solvent (prepared according to the mass ratio of ethylene carbonate (EC) / propylene carbonate (PC) / diethylene carbonate (DEC) / ethyl methyl carbonate (EMC)=1:1:1:2), 0.01wt% lithium hexafluorophosphate, 0.1wt% glutaric anhydride, 1wt% vinyl sulfate and 1wt% vinylene carbonate. The molar ratio of the anhydride organic compound to the lithium salt is 13.21.
[0050] Example 5
[0051] This embodiment provides an electrolyte, including 14.9wt% sodium hexafluorophosphate, 64.5wt% solvent (prepared according to the mass ratio of ethylene carbonate (EC) / propylene carbonate (PC) / diethylene carbonate (DEC) / ethyl methyl carbonate (EMC) = 1:1:1 / :2), 0.5wt% lithium hexafluorophosphate, 5wt% glutaric anhydride, 1wt% vinyl sulfate and 1wt% vinylene carbonate. The molar ratio of the anhydride organic compound to the lithium salt is 13.21.
[0052] Comparative Example 1
[0053] This comparative example provides an electrolyte, which refers to the electrolyte in Example 1, except that no lithium salt and anhydride organic compound are added, and the lack of the two is supplemented by the solvent.
[0054] Comparative Example 2
[0055] This comparative example provides an electrolyte, which refers to the electrolyte in Example 1, except that no anhydride organic compound is added, and the missing mass is supplemented by a solvent.
[0056] Comparative Example 3
[0057] This comparative example provides an electrolyte, which refers to the electrolyte in Example 1, except that no lithium salt is added and the missing mass is supplemented by a solvent.
[0058] Comparative Example 4
[0059] This comparative example provides an electrolyte, which is similar to the electrolyte in Example 1, except that the amount of glutaric anhydride added is 0.3 wt %, and the missing mass is supplemented by solvent. The molar ratio of the anhydride organic compound to the lithium salt is 4.
[0060] Comparative Example 5
[0061] This comparative example provides an electrolyte, which is the electrolyte in Example 1, except that the amount of glutaric anhydride added is 6wt%, the amount of solvent added is changed to 77wt%, and the other components remain unchanged. The molar ratio of the anhydride organic compound to the lithium salt is 79.9.
[0062] Performance Testing:
[0063] Preparation of sodium-ion batteries for testing:
[0064] Preparation of positive electrode sheet: 4800g sodium vanadium phosphate, 150g polyvinylidene fluoride, and 50g conductive carbon black were wet homogenized with N-methylpyrrolidone as solvent. The slurry was evenly dispersed with a viscosity of 5000-6000mPa·s. It was coated on both sides of carbon-coated aluminum foil with a surface density of 160g / m on each side. 2 , and then roller compaction, compaction density is 1.56kg / m 3 , and then die-cut and bake in sequence; the designed single-sided capacity density is 8.45Ah / m 2 .
[0065] Preparation of negative electrode: 4800g of hard carbon, 100g of polyvinylidene fluoride, and 100g of conductive carbon black were wet homogenized with N-methylpyrrolidone as solvent. The slurry was evenly dispersed with a viscosity of 2000-4000mPa·s. It was coated on both sides of the carbon-coated copper foil with a surface density of 62g / m on each side. 2 , and then roll compaction, compaction density is 0.83kg / m 3 , and then die cutting and baking. The designed single-sided capacity density is 9.22Ah / m 2 .
[0066] Diaphragm: The diaphragm is Celgard 2320 model diaphragm, PP-PE-PP material, 20um thick;
[0067] The above positive electrode sheet, negative electrode sheet, separator and electrolyte to be tested are assembled into a 5Ah soft pack battery. Then it is placed in a room at 45°C for 48 hours, and then placed in a room temperature environment for 12 hours; then it is formed, the pressure is controlled to 0.8MPa, the temperature is 35°C, and it is charged to 3.65V at a constant current of 0.5A, and then discharged to 2V at a constant current of 0.5A, and then charged at a constant current of 0.5A for 7 hours, and the formation is completed. After the final packaging, it is used to test the electrochemical performance.
[0068] The electrolytes obtained in Examples 1-5 and Comparative Examples 1-5 were used as the electrolytes to be tested to prepare sodium ion batteries for testing.
[0069] The cycle performance of the sodium ion batteries obtained in Examples 1-5 and Comparative Examples 1-5 was tested:
[0070] Place the sodium ion battery in a constant temperature room, control the temperature between 25±5℃, and let it stand for 30 minutes to allow the sodium ion battery to reach room temperature. Charge the sodium ion battery that has reached constant temperature with a constant current of 1C to 3.65V, then charge it with a constant voltage until the current drops to 0.05C, and then discharge it with a constant current of 1C to 2V. Repeat this cycle, record the discharge capacity of the first cycle and the discharge capacity of the last cycle, and calculate the capacity retention rate according to the following formula:
[0071] The nth cycle capacity retention rate (%) = (nth cycle discharge capacity / first cycle discharge capacity) × 100%
[0072] The test results are shown in Table 1.
[0073] In addition, the present disclosure also provides a comparison chart of the discharge capacity retention rate of the sodium ion batteries obtained in Examples 1-5 and Comparative Examples 1-5, as shown in Figure 1 shown.
[0074] Table 1
[0075] First cycle discharge capacity / Ah Capacity retention rate after 800 cycles Example 1 5.03 97.02% Example 2 5.02 96.36% Example 3 5.01 94.21% Example 4 5.03 92.65% Example 5 4.93 91.75% Comparative Example 1 5.03 84.46% Comparative Example 2 4.82 77.10% Comparative Example 3 5.02 86.93% Comparative Example 4 4.95 79.16% Comparative Example 5 4.98 85.03%
[0076] According to Table 1 and Figure 1 It can be seen that the sodium ion battery prepared by using the electrolyte disclosed in the present invention can effectively improve the cycle performance. The capacity retention rate after 800 cycles is still above 91%.
[0077] The electrolyte cycle performance of Comparative Example 1 in which no lithium salt and anhydride organic compound are added is poor.
[0078] In Comparative Example 2, only lithium salt was added. It can be seen that not only the capacity will be reduced, but also the decay rate of the cycle will be accelerated. This is because the SEI film contains more lithium fluoride components, which affects the migration of sodium ions and covers up some of the active sites for sodium storage in the negative electrode. When the battery cell reaches the set upper limit of charging voltage, sodium precipitation will inevitably occur on the negative electrode side. Sodium reacts with the electrolyte by side, consuming the sodium element that can be charged and discharged as a whole in the battery cell, resulting in low capacity.
[0079] In Comparative Example 3, only anhydride organic compounds were added, which slightly improved the cycle performance compared with Comparative Example 1, but the improvement on the cycle performance was very limited compared with the electrolyte disclosed in the present invention.
[0080] In Comparative Example 4, the molar ratio of the anhydride organic compound to the lithium salt is too small, indicating that a certain proportion of LiF still exists in the SEI film, thereby affecting the capacity of the battery and resulting in limited improvement in the cycle performance.
[0081] In Comparative Example 5, the molar ratio of the anhydride organic compound to the lithium salt is too large, and a certain amount of sodium ions are consumed in the film formation process, resulting in a reduction in capacity. In addition, since the film is thicker, the impedance is increased, and there is a risk of sodium precipitation during charging, which affects the cycle performance to a certain extent.
[0082] In the electrolyte formula of the battery cell of Example 1, the addition amount of lithium hexafluorophosphate is 0.1wt%, and the addition amount of glutaric anhydride is 0.5wt%. From the perspective of battery performance, there is no negative impact on the battery capacity, and the cycle performance is the best, indicating that it is the best addition ratio in this battery system and when matching other electrolyte components.
[0083] Example 2 reduces the amount of glutaric anhydride added on the basis of Example 1, so that the molar ratio of the anhydride organic compound to the lithium salt is reduced to close to 5:1. From the perspective of cycle performance, it is still greatly improved over that of Comparative Example 1, indicating that this ratio can also have a good effect.
[0084] Example 3 increases the amount of glutaric anhydride added on the basis of Example 1, so that the molar ratio of the anhydride organic compound to the lithium salt is close to 20:1. In terms of cycle performance, it is still greatly improved over Comparative Example 1.
[0085] In Example 4, the addition amounts of lithium salt and anhydride organic compound are both lower limits, which do not affect the battery capacity, but still improve the cycle performance to a certain extent.
[0086] In Example 5, the addition amounts of lithium salt and anhydride organic compound are both upper limit values. It can be seen that the capacity of the battery cell is affected to a certain extent, but the cycle performance is improved to a certain extent.
[0087] In combination with Comparative Example 4, Comparative Example 5, Example 1, Example 2 and Example 3, the molar ratio of the anhydride organic compound to the lithium salt has a lower limit. When the molar ratio is lower than 5, the proportion of LiF in the SEI film increases, affecting the battery performance. When the molar ratio is ≥ 5 and the amount of the anhydride organic compound added is less than 5wt%, there is little change in the cycle performance. This is because in addition to synergistically generating the SEI film with lithium ions, glutaric anhydride can also play a film-forming role as an additive. The generated SEI film is only thickened, but the cycle performance is still significantly improved. When the addition ratio of glutaric anhydride is greater than 5wt%, it can be seen that excessive glutaric anhydride significantly affects the capacity and cycle performance of the battery, and the advantage is not obvious compared with Comparative Example 1.
[0088] It should be noted that the ratio of additives in the electrolyte is different from the amount of additives actually injected into the battery cell. The data conclusions of the embodiments and comparative examples are drawn based on a specific injection coefficient. If the positive / negative electrode system, injection coefficient and other parameters are changed, the optimal ratio of additives in the electrolyte may change.
[0089] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0090] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An electrolyte, characterized in that: In terms of mass percentage, it comprises 5-20wt% of sodium salt, 70-94wt% of solvent, 0.01-0.5wt% of lithium salt, 0.1-5wt% of anhydride organic compound and 0.1-5wt% of film-forming additive; The molar ratio of the anhydride organic compound to the lithium salt is not less than 5.
2. The electrolyte according to claim 1, characterized in that In terms of mass percentage, it comprises 5-20wt% of sodium salt, 75-90wt% of solvent, 0.05-0.5wt% of lithium salt, 0.25-5wt% of anhydride organic compound and 1-3wt% of film-forming additive; The molar ratio of the acid anhydride organic compound to the lithium salt is 5-25.
3. The electrolyte according to claim 1 or 2, characterized in that The sodium salt includes one or more of sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium hexafluoroantimonate, sodium difluorooxalatoborate, sodium bis(difluoromalonate)borate, sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethanesulfonyl)imide.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, cyclopentane, dimethyl sulfoxide, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, methyl difluoroacetate, ethyl difluoroacetate, γ-butyrolactone, γ-valerolactone or δ-valerolactone.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium hexafluoroantimonate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate or lithium fluoride.
6. The electrolyte according to any one of claims 1 to 5, characterized in that: The acid anhydride organic compound includes one or more of glutaric anhydride, citraconic anhydride, maleic anhydride, phenyl maleic anhydride, benzoic anhydride or succinic anhydride.
7. The electrolyte according to any one of claims 1 to 6, characterized in that The film-forming additive includes one or more of vinylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, dimethyl sulfate, vinyl sulfate, methyl vinyl sulfate, propylene sulfate, vinyl sulfite, succinic anhydride, biphenyl, biphenyl ether, toluene, xylene, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, propylene sultone, butane sultone, methylene disulfonate, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, heptamethyldisilazane, dimethyl methylphosphonate, diethyl ethylphosphonate, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, triphenyl phosphite, tris(trimethylsilyl)borate or tris(trimethylsilyl)phosphate.
8. A sodium ion battery, characterized in that: The invention comprises a shell, and a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte as claimed in any one of claims 1 to 7 arranged in the shell.